A3.10 IL-6 Receptor Blockade Enhances CD39+ Regulatory T-Cell Development in Rheumatoid Arthritis and in Experimental Arthritis. (25th February 2013) - Thiolat, Allan; Biton, Jerome; Semerano, Luca; Pers, Yves-Marie; Portales, Pierre; Lemeiter, Delphine; Decker, Patrice; Jorgensen, Christian; Boissier, Marie-Christophe; Louis-Plence, Pascale; Bessis, Natacha
Abstract : Background and Objectives: Studies have demonstrated the clinical efficacy of tocilizumab, a humanised anti-IL-6 receptor (R) antibody (Ab), in patients with rheumatoid arthritis (RA). The rational for blocking IL-6 in this disease mainly lays on the pro-inflammatory role of this cytokine in the disease. However, only few works have studied the consequences of anti-IL-6R treatment on Tregs cells and mainly focuses on their frequency. Our objective was to elucidate anti-IL-6R mode of action on Tregs in RA patients treated with tocilizumab and in a RA model. Methods: Mice with collagen-induced arthritis (CIA) were treated at day 0 by MR16–1 (a rat anti-mouse IL-6 receptor monoclonal Ab provided by Chugai Pharmaceutical Co. LTD, Japan) and the evolution of CD4 + FoxP3 + Tregs during arthritis course was assessed at key time points (day 8–18–28 and 42 after CIA induction) by studying their number, frequency and phenotype (expression of GITR, ICOS, Helios, CD62L, CTLA-4 and CD39) in lymph nodes (LN), thymus and spleen by flow cytometry. Numerical analysis of Th17 and Th1 cells was also performed by flow cytometry. Twenty patients with severe and active RA were recruited and treated with 8 mg/kg of tocilizumab monthly. Peripheral blood was recovered at day 0, as well as 1 and 3 month, and Th17and Tregs were analysed by flow cytometry. Results: Clinical and histological evaluation of arthritides in mice treated with anti-mouse IL-6R mAb showed, as expected, a less severe disease as compared to control Ig treated mice. Th17 frequency was unchanged, but Tregs frequency was enhanced in the LN of MR16–1 treated mice. In the thymus, we observed an enhanced frequency of Tregs CD4 + CD8 − FoxP3 + . Tregs phenotype was also modified in treated mice, with an increased frequency of CD39 + Tregs (LN and spleen), suggesting an enhanced ATP hydrolysis immunosuppressive activity of Tregs. In RA patients, Th17 frequencies were not modified by tocilizumab therapy and did not differ between responders and non-responders. Interestingly, CD39 + Treg cell among CD4 + cells frequencies were significantly higher in responders than in non-responders after 3 months of tocilizumab therapy. Conclusions: Tregs, but not Th17, are modified by anti-IL-6R treatment in both CIA and RA. These results support a beneficial effect in RA of treatments responsible for CD39 + Tregs enhancement and emphasise the relevance of the monitoring cell populations after cytokine blockade used to treat arthritis.